PENINGKATAN KUALITAS PELAYANAN MELALUI PELATIHAN SADAR WISATA DI KAWASAN PARIWISATA SENGGIGI KABUPATEN LOMBOK BARAT - Abdurrahman, Abdurrahman; Rinuastuti, Baiq Handayani; Dakwah, Muhammad Mujahid; Muhtarom, Zamroni Alpian; Supryadi, Didy Ika; Putra, Taufan Handika (Universitas Mataram, 2024)
The purpose of this community service program is to increase understanding to training participants, especially tourism actors in Senggigi Village to provide the best service to tourists. The training methods provided include management and arrangement of tourist attractions, hospitality and conducting Focus Group Discussions (FGDs) in order to increase public awareness of tourism in the Senggigi Area. The results of the training showed that participants got a good understanding of awareness in maintaining a sustainable tourism area by making a program plan to improve the quality of tourist attraction services based on Sapta Pesona in the Senggigi tourism area. Through this service activity, participants were able to compile and convey ideas and aspirations to stakeholders or the local government.